SYNTHESIS OF SOME NOVEL SCHIFF BASE CONTAINING [1,2,4] TRIAZOLO RING - ANIL V PATEL; JITESH H TAILOR; G. M. MALIK (International Journal of Pharma and Bio Sciences, 2014)
4-amino-5-biphenyl-4-yl-4H-[1, 2, 4] triazolo-3-thiols have been prepared from biphenyl-4-carboxyclic acid (1), carbon disulphide (CS2) and hydrazine hydrate. The resulting 4-amino-5-biphenyl-4-yl-4H-[1, 2, 4] triazolo-3-thiol was treated with substituted aromatic aldehydes to give the Schiff base. The synthesized compounds were characterized by elemental and spectral analysis (IR, 1H NMR and mass spectrometry). All synthesized compounds were screened for their in vitro antimicrobial activity against bacterial strains and fungi strain and found to have significant effect against the tested microorganisms.